Vampire zombies from space! [videorecording (DVD)] - Hart, David Liebe; Kauffman, Lloyd; Bee, Andrew (Cleopatra Entertainment, 2026)
The film is a parody of 1950s horror and sci-fi B-movies which blends satire, crude humour, and slapstick with practical effects, miniatures and classic horror tropes. The film centres around an ensemble cast of comedically cliché characters trying to defend a small American town from Dracula, and his army of vampire zombies.